An Older and More Beautiful Belgrade - Prodanović, Mileta (Central European University Press, 2023)
This substantial essay depicts urban collapse in an exceptionally difficult period of the Serbian capital. The author has marshalled facts, reflections, photographs and other imagesto demonstrate the transformation of Belgrade during the Milošević years. With the theoretical grounding of cultural anthropology, history studies, culture of memory, history of art, and urbanism, Mileta Prodanović considers changes to the built environment and urban landscape in the city in the 1990s. He covers many visual aspects of life with great ingenuity: shopping centers, unregulated construction and “wild” modifications of buildings, new buildings (broadcasting studios, shops, homes) that do not fit the surroundings, bad taste in home furnishings (camp, kitsch), boondoggles such as the international art center, problematic historical markers like the obelisk of the eternal flame, billboards, store displays, electoral propaganda, graffiti, grave-markers and cemetery memorials, coins and paper money, calendars, beer labels, and even religious icons (and more). All this information is provided with some critique and much implied comparison to past standards.